COVID‐19 policies in Germany and their social, political, and psychological consequences. (28th September 2020) - Naumann, Elias; Möhring, Katja; Reifenscheid, Maximiliane; Wenz, Alexander; Rettig, Tobias; Lehrer, Roni; Krieger, Ulrich; Juhl, Sebastian; Friedel, Sabine; Fikel, Marina; Cornesse, Carina; Blom, Annelies G.
Abstract: Many policy analyses on COVID‐19 have been focusing on what kind of policies are implemented to contain the spread of COVID‐19. What seems equally important to explore are the social and political consequences of the confinement policies. Does the public support strict confinement policies? What are the social, political, and psychological consequences of the confinement policies? The question of how legitimate a policy is among the public is at the core of democratic theory. Its relevance also stems from the expected consequences of public support on behavior: The more someone supports a policy, the more someone is likely to follow the policy even if the policy is not strictly enforced. In this paper, we will focus on Germany, briefly summarize the main policies during the first 6 weeks of confinement and then explore political attitudes, risk perceptions, and the social consequences of the lockdown.